Comparative Analysis of Road Network Simulation Model Performance of Pahlawan Road Area - Zein, Fikri Haikal; Muhammadun, Haris; Marleno, Risma (International Journal of Social Science and Community Service, 2024)
The solution to the transportation problem lies in assessing the performance of related road sections and intersections, and analyzing different traffic management schemes to optimize efficiency. This study aims to compare the performance of a road network simulation model for the Pahlawan road area. Data analysis includes examining origin-destination matrices, vehicle free speeds, vehicle behavior, and intersection control. The simulation model, calibrated and validated using Vissim, represents real-world conditions. Implementing SLFF (Single Lane Free Flow) and MLFF (Multi Lane Free Flow) systems at toll gates (scenarios 1 and 2) reduced queues, particularly at the Pancasila Monument Roundabout and Jalan Jati Raya. Adding a new toll gate via Jalan Kahuripan further improved traffic on Jalan Pahlawan compared to scenarios 1 and 2. However, converting the Gelora Delta roundabout into an underpass without additional measures worsened toll gate queues. Effective traffic performance can be achieved by combining the Gelora Delta roundabout underpass with either the SLFF toll payment system (scenario 5), MLFF (scenario 6), or the addition of a new toll gate (scenario 3).